Situation Report: Hungary, 19 September 1978 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Pension System Criticized, Basic Changes Proposed The Regulation of Western Investment in Eastern Europe Kindergartens Start a Crucial Year Agromas: Specialization in Name Only? Strengthening of Dutch-Hungarian Relations